2021
DOI: 10.1186/s40345-021-00225-5
|View full text |Cite
|
Sign up to set email alerts
|

‘Pediatric Bipolar Disorder’ rates are still lower than claimed: a re-examination of eight epidemiological surveys used by an updated meta-analysis

Abstract: Background ‘Pediatric bipolar disorder’ (PBD) is a controversial diagnosis with varying rates of clinical diagnosis. A highly cited meta-analysis (Van Meter et al. 2011) of a dozen epidemiological surveys suggested a global community prevalence of PBD of 1.8%. This was updated to 3.9% with eight additional surveys (Van Meter et al. 2019a). In terms of the Cochrane Handbook for Systematic Reviews of Interventions, the heterogenous community surveys were arguably unsuitable for statistical meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
9
0
2
Order By: Relevance
“…A separate meta-analysis focusing on children aged 12 or younger in community samples identified only a single case of bipolar disorder worldwide, yielding a prevalence of <0.02% and challenging claims of its ubiquity (Douglas & Scott, 2014). Reexamination of Van Meter et al's data focusing on children and younger adolescents similarly showed very low rates, albeit slightly higher in the USA (Parry et al, 2018(Parry et al, , 2021. A further limitation of the Van Meter et al papers was that analyses grouped different types of bipolar disorder together, despite the diverse diagnostic criteria used across studies, likewise complicating interpretation of their findings (Carlson, 2018;Parry et al, 2018;Duffy, 2019;Parry et al, 2019aParry et al, , 2021.…”
Section: Clinical Descriptionmentioning
confidence: 97%
See 1 more Smart Citation
“…A separate meta-analysis focusing on children aged 12 or younger in community samples identified only a single case of bipolar disorder worldwide, yielding a prevalence of <0.02% and challenging claims of its ubiquity (Douglas & Scott, 2014). Reexamination of Van Meter et al's data focusing on children and younger adolescents similarly showed very low rates, albeit slightly higher in the USA (Parry et al, 2018(Parry et al, , 2021. A further limitation of the Van Meter et al papers was that analyses grouped different types of bipolar disorder together, despite the diverse diagnostic criteria used across studies, likewise complicating interpretation of their findings (Carlson, 2018;Parry et al, 2018;Duffy, 2019;Parry et al, 2019aParry et al, , 2021.…”
Section: Clinical Descriptionmentioning
confidence: 97%
“…Many studies classed it within 'bipolar disorder not otherwise specified' using DSM IV criteria (Axelson et al, 2011), which can be met in various ways and so is more ill-defined. Other studies (Wozniak et al, 2017) diagnosed children with ultradian cycling as having 'bipolar I' despite this not being standard DSM criteria, representing a further blurring of diagnostic boundaries (Parry et al, 2021). Adopting strict DSM criteria, however, does not solve these problems: DSM 5 field trials were unsuccessful for the diagnosis of bipolar disorder in children and unable to obtain an accurate estimate of inter-rater reliability due to large variability (Regier et al, 2013).…”
Section: Clinical Descriptionmentioning
confidence: 99%
“…3 Van Meter and colleagues furnished their detractors a robust rebuttal, 4 but the exchange also prompted them to conduct a further meta-analysis in 2019 that updated their findings. 5 However, their findings and arguments were once again comprehensively critiqued by Parry and colleagues 6 and no compromise was achieved. Thus this important debate concerning the definition of PBD-the issue at the heart of its prevalence-remains unresolved and the seemingly simple question lacks a satisfactory answer.…”
Section: The Prevailing Questionmentioning
confidence: 99%
“…In their review, Parry et al 6 identify and systematically address key problems within epidemiological research that, in our view, are at least in part due to the fundamental flaws in our current diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in familial at-risk populations (eg, offspring of individuals affected by BD) and youth affected by BD similarly reported altered amygdala, striatal, CEN, and VAN or SN activity and altered amygdala-VAN and amygdala-SN functional connectivity during emotion processing and emotional regulation . Yet, although childhood-onset BD is a more severe form of BD, it is less common than adult-onset BD . Thus, there remains a critical need for studies to examine young adults at risk of mania/hypomania .…”
Section: Introductionmentioning
confidence: 99%